Supporting the spirituality of older people living with dementia in nursing care: A hermeneutic phenomenological inquiry into older people's and their family members' experiences - Toivonen, Kristiina; Charalambous, Andreas; Suhonen, Riitta (My University, 2023)
Supporting spirituality is an essential aspect of the holistic nursing care of older people living with dementia. Spirituality is defined as a search for answers to questions about the meaning and purpose of life and the individual's relationship with the sacred or transcendent. This relationship may or may not involve an affiliation with a specific religion.
Keywords: Ricoeur; Dementia; Hermeneutic phenomenology; Older people nursing; Qualitative study; Supporting spirituality